The domain of syntax - Anderson, John M. (John Mathieson), 1941- (Oxford : Oxford University Press, 2011)
This volume explores the consequences for syntax of assuming that language is grounded in cognition and perception. He considers whether this permits a lexicalist approach to syntax that would allow it to dispense not only with structural mutations but with universal grammar itself.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Finiteness (Linguistics)